If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 42 = 3(3m + -4) Reorder the terms: 42 = 3(-4 + 3m) 42 = (-4 * 3 + 3m * 3) 42 = (-12 + 9m) Solving 42 = -12 + 9m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-9m' to each side of the equation. 42 + -9m = -12 + 9m + -9m Combine like terms: 9m + -9m = 0 42 + -9m = -12 + 0 42 + -9m = -12 Add '-42' to each side of the equation. 42 + -42 + -9m = -12 + -42 Combine like terms: 42 + -42 = 0 0 + -9m = -12 + -42 -9m = -12 + -42 Combine like terms: -12 + -42 = -54 -9m = -54 Divide each side by '-9'. m = 6 Simplifying m = 6
| (2x-y)dx+(2x+y)dy=0 | | 3(2b-2)=6(1+3b) | | (2xy-y^2)dx-x^2dy=0 | | C/d=x | | .50x+.75y=20 | | -6r-29=-5(2+5r) | | 6y+1=-13 | | 11(x-6)=-11 | | r=(7+B)m | | 8x+2=5x-6 | | 11(x-6)=11 | | -4(1-4v)-v=-4-2v | | 5(x-6)=-10 | | -(3n-5)=-5n-7 | | lnx*sin^3*y*dx+x*cosy*dy=0 | | z^2+6z+20=0 | | 5a-5=6(-4a+4) | | (x-y)ydx-x^2dy=0 | | 16lw=v | | 2x^2-3xy-2y^2-2x-11y-12=0 | | 5-3x=14+2x | | 5x-3(x-5)+9(y-5)= | | x^4-9x+7=0 | | x^4-8x^3+9x^2+28x-60=0 | | -9+n=-2(-3-2n) | | 4m+9=7m+12 | | y^4+2y^2+1=0 | | 2(-5r-6)=-12-6r | | 8x+19=26 | | 4x+2=9-2x | | 4(5x+2)=-24+4x | | 3(k-3)-5=7k-(3k-2) |